1983
DOI: 10.1289/ehp.8351267
|View full text |Cite
|
Sign up to set email alerts
|

The advantages and limitations of an in vivo test system for investigating the cytotoxicity and fibrogenicity of fibrous dusts.

Abstract: The acute response of the rat lung to a range of fibrous materials has been investigated by bronchopulmonary lavage, at dose levels of 0.5 and 1.0 mg, 1 and 7 days after their administration by intratracheal instillation. The materials chosen for study included UICC chrysotile A, amosite, crocidolite and anthophyllite, and samples of S. African "long" amosite and glass fiber. In addition, the subacute response to 1, 2 and 3 mg of chrysotile and amosite has been studied at 50 and 100 days after instillation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…For group II, the histopathological examination of the trachea and main bronchia has shown for cases 10,11,12,13, and 16 the presence of a nodular inflammatory infiltrate with lymphocytes, hystiocytes, rare macrophages, and neutrophils in the submucosa (62, 5%). In some histological sections, the lymphohystiocitary infiltrate extended from the subepithelial layer to the muscular layer of the trachea and main bronchia.…”
Section: Resultsmentioning
confidence: 99%
“…For group II, the histopathological examination of the trachea and main bronchia has shown for cases 10,11,12,13, and 16 the presence of a nodular inflammatory infiltrate with lymphocytes, hystiocytes, rare macrophages, and neutrophils in the submucosa (62, 5%). In some histological sections, the lymphohystiocitary infiltrate extended from the subepithelial layer to the muscular layer of the trachea and main bronchia.…”
Section: Resultsmentioning
confidence: 99%
“…Another methodological limitation in the earlier experiments was due to the low fiber number remaining after 1 and 2 years, necessitating very long and tedious examination of the SEM and TEM photographs of the filtered fibers. Parts of the earlier study (4) suggested to achieve optimum dust distribution with a limitation of the doses administered to a maximum of 0.6 mg/g fresh ie after intratracheal weight of lung (18).…”
Section: Resultsmentioning
confidence: 99%
“…It is not established whether these effects on the lung are a consequence only of the silica present in most bentonites or are a general property of the bentonite mineral mix. Intratracheal administration of bentonite to rats revealed a high cytotoxic potential; however, the acute inflammatory response was short-lived and the cell population returned to normal within few weeks (Sykes et al, 1983;Vallyathan, 1994). These studies did not consider chronic exposure.…”
Section: 3mentioning
confidence: 98%